2016
DOI: 10.1371/journal.pone.0151873
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Screening of Digestion Tract Toxic Genes in Proteus mirabilis

Abstract: Proteus mirabilis is a common urinary tract pathogen, and may induce various inflammation symptoms. Its notorious ability to resist multiple antibiotics and to form urinary tract stones makes its treatment a long and painful process, which is further challenged by the frequent horizontal gene transferring events in P. mirabilis genomes. Three strains of P. mirabilis C02011/C04010/C04013 were isolated from a local outbreak of a food poisoning event in Shenzhen, China. Our hypothesis is that new genes may have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
2
19
3
Order By: Relevance
“…According to the investigation of SZCDC, P. mirabilis C02011 was isolated from the residue food (cold dishes), vomited matter, excrement, and anal swab of the patients. Results of pulsed-field gel electrophoresis (PFGE) indicated that P. mirabilis C02011 was associated with this food poisoning case (Shi et al, 2016).…”
Section: Bacterial Strains Isolation and Culturementioning
confidence: 99%
See 4 more Smart Citations
“…According to the investigation of SZCDC, P. mirabilis C02011 was isolated from the residue food (cold dishes), vomited matter, excrement, and anal swab of the patients. Results of pulsed-field gel electrophoresis (PFGE) indicated that P. mirabilis C02011 was associated with this food poisoning case (Shi et al, 2016).…”
Section: Bacterial Strains Isolation and Culturementioning
confidence: 99%
“…In our study, food samples, stool specimens, and vomit specimens collected from the patients were sent to the laboratory for examination within 24 h. Based on the phenotypic properties of morphology and biochemical features (WS/T 9-1996: Diagnostic criterion and principles of food poisoning induced by P. mirabilis; GB/T4789-2003: National criterion for food microbiological examination), P. mirabilis was successfully identified from the food poisoning incident (Shi et al, 2016). Meanwhile, Sensititre Auto-reader (Sensititre, United Kingdom) system was used to detect the bacteria.…”
Section: Bacterial Strains Isolation and Culturementioning
confidence: 99%
See 3 more Smart Citations